The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1089/vbz.2006.6.266
|View full text |Cite
|
Sign up to set email alerts
|

Cats and Goat Whey Associated with Toxoplasma gondii Infection in Pigs

Abstract: In organic livestock production systems, farm-management factors are thought to play an important role in the on-farm prevalence of Toxoplasma gondii. Serological results and the results of an HACCP analysis were combined to determine important risk factors for the prevalence of this protozoan parasite. Mathematical analysis demonstrated that feeding goat whey to pigs and the presence of a high number of cats were positively correlated to T. gondii seroprevalence in pigs. Not covering roughage and the farmers'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 19 publications
4
34
0
Order By: Relevance
“…The presence of cats and contamination of feed and water are well known risk factors for T. gondii infection (Garcia-Bocanegra et al, 2010;Meerburg et al, 2006). Although no significant associations were found in this study, our results are aligned with risk factors reported in previous studies: the relative risk of being positive was higher in those farms having cats or practices that increase the potential of feed contamination with cat's faeces.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The presence of cats and contamination of feed and water are well known risk factors for T. gondii infection (Garcia-Bocanegra et al, 2010;Meerburg et al, 2006). Although no significant associations were found in this study, our results are aligned with risk factors reported in previous studies: the relative risk of being positive was higher in those farms having cats or practices that increase the potential of feed contamination with cat's faeces.…”
Section: Discussionsupporting
confidence: 89%
“…This knowledge is essential for the future implementation of Hazard Analysis and Critical Control Points (HACCP) allowing the farmers to develop efficient and sustainable control measures against T. gondii infection for their farms (Kijlstra et al, 2009;Meerburg et al, 2006).…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…For example, in intensively managed swine farms, modern biosecure management practices have resulted in reduced levels of infection in swine raised in confinement [96,179,180]. In organic livestock production systems, farmmanagement factors including feeding are thought to play an important role in the on-farm prevalence of T. gondii [181]. To limit T. gondii infection in such farms, recommended practices include exclusion of cats or other wildlife, strict rodent control and restriction of human entry in pig barns [182].…”
Section: Conclusion: Consequences For the Management Of Zoonotic Tranmentioning
confidence: 99%
“…The cases of cannibalism by the accidental access to preliminary dead animals, especially when animal tissues are buried or composted are considerably common [41,44,49,71]. Similarly, providing drink water of unknown quality to the pigs, possibly contaminated with the oocysts and feeding of raw animal products such as goat whey is also a potential risk, if made from unprocessed milk containing tachyzoites from a recently infected animal undergoing the dissemination phase [42,75].…”
Section: Risk Factors Associated With the Porcine Toxoplasmosismentioning
confidence: 99%